A Literature Review of EFL Students’ Perspectives on Using ChatGPT to Learn Reading: Benefits and Challenges - Tapyor, Dece (Transpublika Publisher, 2025)
One essential ability that requires development is reading. Thus, it is crucial to learn the positive and negative consequences of incorporating platforms like ChatGPT into reading in English as a foreign language (EFL) and practice, and to address learning difficulties that may arise in understanding information. Hence, the research examines the benefits and challenges of using ChatGPT to learn reading skills. However, the author reviews 20 empirical studies published in peer-reviewed journals between 2023 and 2025, using Google Scholar, to achieve that goal. The analysis results were categorized into five themes summarizing each ChatGPT’s benefits and challenges related to EFL students’ reading experiences. The first three themes were associated with the potential benefits of integrating ChatGPT to learn reading skills. Those themes were: (1) ChatGPT provides EFL learners with fast replies, (2) ChatGPT helps EFL learners to understand unfamiliar words, and (3) ChatGPT supports EFL learners in improving their reading skills. The other themes concerned the challenges of using ChatGPT to develop reading skills. Those themes were: (4) ChatGPT prevents EFL learners from thinking critically, and (5) ChatGPT provides EFL learners with unclear information. The researcher discusses themes in light of the relevant literature and presents recommendations for future research.